Response of Vitis vinifera L. cv. Merlot to Low Frequency Drip Irrigation and Partial Root Zone Drying in the Western Cape Coastal Region – Part I. Soil and Plant Water Status - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2011)
The impact of five drip irrigation strategies on water status in Merlot/99R was compared to a non-irrigated control (T1) in the coastal wine grape region of the Western Cape province, South Africa. Relationships between predawn (ΨPD), leaf (ΨL), stem (ΨS) and total diurnal (ΨTot) water potential made it possible to classify grapevine water status in terms of ΨL, ΨS, or ΨTot according to previous classifications derived from ΨPD. Around véraison, T1 grapevines already experienced moderate to strong water constraints (ΨS < -1.0 MPa), followed by strong to severe water constraints (ΨS < -1.4 MPa) prior to harvest. Irrigations at pea size, véraison and post-harvest, either applied in grapevine rows (T2) or work rows (T4), did not reduce water constraints compared to T1. However, irrigations at pea size, midway between pea size and véraison, at véraison, midway between véraison and harvest, and post harvest, either applied in grapevine rows (T3) or work rows (T5), reduced grapevine water constraints compared to T1. Irrigation in work rows did not affect grapevine water status compared to irrigation in grapevine rows. A partial root zone drying (PRD) strategy, obtained by switching subsurface irrigation in work rows between alternating rows at approximately 14-day intervals (T6), also reduced water constraints compared to T1. The water status in PRD grapevines clearly responded to the low plant available water (PAW) depletion levels in the alternating work rows in which irrigations were applied. There was minimal lateral flow of irrigation water from subsurface irrigation lines in the work rows towards the grapevine rows.